Enhancing Competitiveness Business Strategy of Organic Vegetables Using Analytical Hierarchy Process (AHP) - Pristiana Widyastuti (DeReMa (Development Research of Management): Jurnal Manajemen, 2017)
Public awareness about healthy lifestyles leads people to want to understand more about the food they consume. Choosing organic vegetables is one alternative choices when seeking to have a healthy body and healthy lifestyle. Unfortunately, not a lot of organic vegetable farmers in Indonesia succeed in seizing the organic vegetable market rather than the non-organic and the competition with imported organic vegetables into Indonesia prevents farmers from thriving. This study aims to: 1) Analyze the factors affecting the competitiveness of the organic vegetables market; 2) Analyze the appropriate strategy for increasing the competitiveness of the organic vegetables market; 3) Analyze the factors priority strategies for improving the competitiveness of the organic vegetables market. Porter's Generic Model and Analysis Analytical Hierarchy Process (AHP) is used to determine the best strategy. The research found that organic vegetables marketing channels are still dominated by conventional market; the higher cost for intensive cultivation of organic vegetables. The main strategies are derived from the analysis is focusing on market delivery. There needs to be retailers of organic vegetables either modern or traditional to display these products. The establishment of organic vegetable outlets and online marketing that are not dependent on large retail (hypermarket) become recommendations in this study.Bahasa Indonesia Abstrak: Kesadaran masyarakat tentang gaya hidup sehat memberi pilihan kepada masyarakat untuk memahami makanan yang mereka konsumsi. Pilihan sayuran organik merupakan salah satu alternatif untuk memiliki tubuh sehat dan gaya hidup sehat bagi masyarakat. Sayangnya, tidak banyak petani sayuran organik di Indonesia yang berhasil merebut pasar sayuran organik daripada non organic. Persaingan produk impor sayuran organik ke Indonesia membuat petani tidak bisa berkembang. Penelitian ini bertujuan untuk: 1) Menganalisis faktor-faktor yang mempengaruhi daya saing pasar sayuran organik; 2) Menganalisis strategi yang tepat untuk meningkatkan daya saing pasar sayuran organik; 3) Menganalisis faktor strategi prioritas untuk meningkatkan daya saing pasar sayuran organik. Model Generik Porter dan Analisis Analytical Hierarchy Process (AHP) digunakan untuk menentukan strategi terbaik. Penelitian ini menemukan bahwa saluran pemasaran sayuran organik masih didominasi oleh pasar konvensional; Biaya yang lebih tinggi untuk budidaya sayuran organik secara intensif. Strategi utama yang didapat dari analisis adalah strategi fokus pada pengiriman pasar. Perlu ada pengecer sayuran organik baik modern maupun tradisional untuk memasarkan produk ini. Pembukaan gerai sayuran organik dan pemasaran online yang tidak tergantung pada ritel besar (hypermarket) menjadi rekomendasi pada penelitian ini.